Multiethnographic Faculty Perspectives on Navigating Writing Support for Students in Higher Education in the Age of GenAI - Gagné, Antoinette; Baxan, Victorina; Danilina, Elena; Fowler, Mary-Ann; Herath, Sreemali; Kang, Phoebe; Kim, Jade; McIntosh, Megan; Shi, Wenyangzi (Journal of Teaching and Learning, 2026)
We are a research collective of nine higher education educators and researchers discussing our perspectives on the impact of generative artificial intelligence (GenAI) tools on the provision of academic writing support to students in higher education. Using a collaborative multiethnographic approach, we employ a narrative writing style that reflects a dialogic approach to our critical reflections on our personal experiences with GenAI within our unique contexts. Our perspectives are examined through the conceptual lenses of positive psychology (MacIntyre et al., 2016) and emotion labour and feeling rules (Benesch, 2018). The ensuing conversation invites our readers to consider with us three questions related to the impact of GenAI in higher education and on student academic writing: how our provision of writing support has changed, what concerns us about GenAI-mediated writing, and what promising practices are being used to incorporate GenAI tools as support for student writing into our pedagogy.